2003
DOI: 10.1046/j.0902-4441.2003.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HFE gene mutations in Iranian beta‐thalassaemia minor patients

Abstract: Our results suggest that HFE mutations C282Y and H63D are more frequent in Iranian BTM patients than in the normal population, causing no significant changes in serum ferritin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…However, as indicated in Table 2, our results are very similar to those reported in India and relatively similar to those reported in Turkey [1][3]. Previous studies have described the prevalence of HFE gene mutations in the Iranian population, in patients with thalassemia, and in a group of diabetics [8][9][10]. The results of both these studies were very similar to ours with regards to H63D.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, as indicated in Table 2, our results are very similar to those reported in India and relatively similar to those reported in Turkey [1][3]. Previous studies have described the prevalence of HFE gene mutations in the Iranian population, in patients with thalassemia, and in a group of diabetics [8][9][10]. The results of both these studies were very similar to ours with regards to H63D.…”
Section: Discussionsupporting
confidence: 91%
“…The results of both these studies were very similar to ours with regards to H63D. However, we did not observe any cases of heterozygotes for C282Y, whereas the frequency of heterozygotes in patients with thalassemia was 3% in a previous study from Iran [8][9][10][11]. …”
Section: Discussionsupporting
confidence: 89%
“…17,5 Previous Iranian studies reported 8.65% allele frequency for the H63D mutation and absence of the C282Y allele in a limited group of random individuals from the Teheran region. 18,19 However, the same authors reported among bone marrow transplanted patients and b-thalassemia carriers from the same region 12.9 and 1.6% allele frequency for the H63D and for the C282Y mutation, respectively.…”
Section: Introductionmentioning
confidence: 81%
“…While significantly higher serum ferritin levels in Italian β-thalassemia carriers with H63D homozygote were observed in one study [10], many others showed no effect on iron loading [9,23,24,25,26]. It has also been shown that the presence of the H63D mutation results in a significant increase in serum transferrin saturation but does not result in significant iron overload [4].…”
Section: Discussionmentioning
confidence: 99%